The Element of Publicity in the Crime of Spreading Electronic Rumors in Accordance With the Provisions of Federal Decree-Law No. (34) Of 2021 Regarding Combating Rumors and Electronic Crimes : A Comparative Analytical Study - Almaeeni, Mayed; Al Nawayse, Abdulellah (Journal of Legal Sciences, 2026)
Publicity in the crimes of spreading rumors is one of the most prominent determinants of the crime, as publicity is the method and method adopted by the perpetrator of the crime of spreading rumors in promoting them in order to achieve the goals he wants. The study aims to shed light on the position of the UAE legislator in Federal Decree-Law No. (34) of 2021 regarding combating rumors and cybercrimes in explaining and defining the element of publicity in the crime of spreading and promoting rumors, and the impact of this element on the elements of crime, and the position of the UAE judiciary towards it. The study relies on the descriptive approach by describing the subject from the quantitative survivor, and the analytical approach by analyzing the position of the UAE legislator and the UAE judiciary on the element of publicity in the crimes of spreading rumors, with a statement of the position of the Egyptian legislator in some places when needed. At the end of the research, we reached an important conclusion that the crime of spreading and promoting rumors is one of the crimes of publicity, meaning that the UAE legislator required the availability of publicity in this crime. At the end of the research, we find it appropriate for the UAE legislator to add the definition of publicity in the first article of the Anti-Rumors and Cybercrime Law, and to indicate its characteristics and means.